Detection of FLT3 Internal Tandem Duplication in Targeted, Short-Read-Length, Next-Generation Sequencing Data - David H. Spencer; Haley Abel; Christina M. Lockwood; Jacqueline E. Payton; Philippe Szankasi; Todd W. Kelley; Shashikant Kulkarni; John D. Pfeifer; Eric J. Duncavage (2012)
A recurrent somatic mutation frequently found in cytogenetically normal acute myeloid leukemia (AML) is internal tandem duplication (ITD) in the fms-related tyrosine kinase 3 gene (FLT3). This mutation is generally detected in the clinical laboratory by PCR and electrophoresis-based product sizing. As the number of clinically relevant somatic mutations in AML increases, it becomes increasingly attractive to incorporate FLT3 ITD testing into multiplex assays for many somatic mutations simultaneously, using next-generation sequencing (NGS). However, the performance of most NGS analysis tools for identifying medium-size insertions such as FLT3 ITD mutations is largely unknown. We used a multigene, targeted NGS assay to obtain deep sequence coverage (>1000-fold) of FLT3 and 26 other genes from 22 FLT3 ITD-positive and 29 ITD-negative specimens to examine the performance of several commonly used NGS analysis tools for identifying FLT3 ITD mutations. ITD mutations were present in hybridization-capture sequencing data, and Pindel was the only tool out of the seven tested that reliably detected these insertions. Pindel had 100% sensitivity (95% CI = 83% to 100%) and 100% specificity (95% CI = 88% to 100%) in our samples; Pindel provided accurate ITD insertion sizes and was able to detect ITD alleles present at estimated frequencies as low as 1%. These data demonstrate that FLT3 ITDs can be reliably detected in panel-based, next-generation sequencing assays.